0676 Sleep Disturbance among Pregnant Women: The Influence of Environmental and Contextual Factors. (12th April 2019) - Dhaliwal, Sammy S; Keller, Jennifer; Le, Huynh-Nhu; Lewin, Daniel S
Abstract: Introduction: Disrupted sleep during pregnancy affects nearly 85% of women. This can contribute to psychological distress and antenatal depression. The aims of the current project were to test whether (a) poorer subjective sleep quality contributed to greater depression and anxiety symptoms, and (b) contextual factors predicted clinically significant sleep disturbance after adjusting for socioeconomic status (SES). Methods: In a mixed-methods study, 418 pregnant women (age: M=32.4 years; gestation: M=28.4 weeks, SD=8.4 weeks; 58% Black) completed the Pittsburgh Sleep Quality Index (PSQI), measures of pregnancy-related physiological factors, and provided details about their sleep environment. They also rated perinatal depression, anxiety, and SES (Hollingshead and MacArthur Ladder). Sixty-two women completed these measures again later in pregnancy (gestation M = 34.2 weeks). A subset of seven women underwent actigraphy (9-nights) during their third trimester. Logistic regressions adjusted for age, BMI, race, sleep disordered breathing, and gestational week. Results: Subjective sleep quality was significantly poorer among Black women and those with higher BMI. Physiological factors (i.e., restless leg syndrome, nocturnal urination, and acid reflux) explained subjective sleep disturbance after accounting for gestational week ( p s<.01). Among women with history of psychopathology (n=221), sleep disturbance was significantly related to anxiety and depression symptoms ( p s<.01), with greater sleep disturbance (PSQI score >5) predicting clinically significant antenatal depression (B = .38, p <.05). However, those who rated their social standing as higher reported lower sleep disturbance throughout pregnancy, even after adjusting for mood and anxiety (B= .86, SE =.41; p <.05). There was a dose-response positive association between sleep disturbance and depression severity among Black women only (B = .89; p <.05). Among lower SES Black women, environmental factors (greater ambient noise and light pollution) partially mediated this effect (B= .45, SE =.17; p <.01). Conclusion: Sociocontextual factors may explain sleep disturbance severity among low-income pregnant Black women, above and beyond traditional metrics of SES. Higher subjective SES may be protective against sleep disturbance and psychiatric distress. Assessments of sleep during pregnancy should account for physiological considerations and environmental disruptions, alongside mood and anxiety. Support (If Any): NIMH (1R36MH118000-01)